An ethnopsychology of idioms of distress in urban Kenya. (August 2019) - Mendenhall, Emily; Rinehart, Rebecca; Musyimi, Christine; Bosire, Edna; Ndetei, David; Mutiso, Victoria
Idioms of distress have become a central construct of anthropologists who aspire to understand the languages that individuals of certain sociocultural groups use to express suffering, pain, or illness. Yet, such idioms are never removed from global flows of ideas within biomedicine that influence how cultural idioms are conceived, understood, and expressed. This article proposes a preliminary model of ethnopsychology described by urban Kenyans, which incorporates local (traditional) and global (biomedical) idioms of distress that are both distinct and overlapping in symptomology and experience. This ethnopsychology was generated from analyzing 100 life history narrative interviews among patients seeking care in a public hospital in Nairobi, Kenya, which explicitly probed into how people experienced and expressed the Kiswahili idioms huzuni (roughly translated as sadness or grief) and dhiki (stress or agony) and English terms stress and depression. Kufikiria sana, or "thinking too much", emerged organically as a powerful cultural idiom and as a symptom or sign of other forms of psychological distress. We propose a preliminary model of ethnopsychology that: 1) highlights social and political factors in driving people to express and experience idioms of distress; 2) reveals how the English terms "stress" and "depression" have been adopted into Kiswahili discourse and potentially have taken on new meaning; 3) suggests that the role of rumination in how people express distress, with increasing severity, is closely linked to the concept of "thinking too much", and; 4) emphasizes how somatization is central to how people think about psychological suffering.